Deworming children for soil-transmitted helminths in low and middle-income countries: systematic review and individual participant data network meta-analysis. Issue 3 (3rd July 2019) - Welch, Vivian Andrea; Hossain, Alomgir; Ghogomu, Elizabeth; Riddle, Alison; Cousens, Simon; Gaffey, Michelle; Arora, Paul; Black, Robert; Bundy, Donald; Castro, Mary Christine; Chen, Li; Dewidar, Omar; et al.
ABSTRACT: Intestinal parasites affect millions of children globally. We aimed to assess effects of deworming children on nutritional and cognitive outcomes across potential effect modifiers using individual participant data (IPD). We searched multiple databases to 27 March 2018, grey literature, and other sources. We included randomised and quasi randomised trials of deworming compared to placebo or other nutritional interventions with data on baseline infection. We used a random-effects network meta-analysis with IPD and assessed overall quality, following a pre-specified protocol. We received IPD from 19 trials of STH deworming. Overall risk of bias was low. There were no statistically significant subgroup effects across age, sex, nutritional status or infection intensity for each type of STH. These analyses showed that children with moderate or heavy intensity infections, deworming for STH may increase weight gain (very low certainty). The added value of this review is an exploration of effects on growth and cognition in children with moderate to heavy infections as well as replicating prior systematic review results of small effects at the population level. Policy implications are that complementary public health strategies need to be assessed and considered to achieve growth and cognition benefits for children in helminth endemic areas.